A review of the fossil Embolemidae (Hymenoptera: Chrysidoidea), with description of seven new species and history of the family. (May 2021) - Perkovsky, Evgeny E.; Olmi, Massimo; Müller, Patrick; Guglielmino, Adalgisa; Jarzembowski, Edmund A.; Capradossi, Leonardo; Rasnitsyn, Alexandr P.
Abstract: The fossil Embolemidae (Hymenoptera: Chrysidoidea) are reviewed. Keys to the genera and species of this family are presented. Five new species of Embolemus are described from Cenomanian Kachin amber (Myanmar), namely: Em. antiquus sp. nov., Em. burmensis sp. nov., Em. cretacicus sp. nov., Em. ohmkuhnlei sp. nov. and Em. zherikhini sp. nov. They are the first Embolemus species recorded from Burmese amber. One new species of Embolemopsis from Barremian Wealden amber (UK), is described: Ep. maryannae sp. nov., the oldest known embolemid wasp and the first hymenopteran described from Wealden amber. The genus Ponomarenkoa is transferred from Dryinidae to Embolemidae. A new species of Ponomarenkoa ( P. burmensis sp. nov.) is described from Cenomanian Kachin amber. The genera of Embolemidae are divided into three groups. The phylogenetic significance of the new species of Embolemidae and the history of the family are discussed. Nymphs of Cixiidae and Achilidae are recorded as hosts of Embolemidae. Possible hosts of fossil embolemids are discussed. For the first time, Achilidae ( Protepiptera kaweckii, from Baltic amber) are recorded as hosts of Dryinidae. Protepiptera kaweckii is also recorded for the first time from Rovno amber.